The CORE study-An adapted mental health experience codesign intervention to improve psychosocial recovery for people with severe mental illness: A stepped wedge cluster randomized‐controlled trial - Victoria J. Palmer; Patty Chondros; John Furler; Helen Herrman; David Pierce; Kali Godbee; Konstancja Densley; Jane M. Gunn (Wiley, 2021)
Abstract Background Mental health policies outline the need for codesign of services and quality improvement in partnership with service users and staff (and sometimes carers), and yet, evidence of systematic implementation and the impacts on healthcare outcomes is limited. Objective The aim of this study was to test whether an adapted mental health experience codesign intervention to improve recovery‐orientation of services led to greater psychosocial recovery outcomes for service users. Design A stepped wedge cluster randomized‐controlled trial was conducted. Setting and Participants Four Mental Health Community Support Services providers, 287 people living with severe mental illnesses, 61 carers and 120 staff were recruited across Victoria, Australia. Main Outcome Measures The 24‐item Revised Recovery Assessment Scale (RAS‐R) measured individual psychosocial recovery. Results A total of 841 observations were completed with 287 service users. The intention‐to‐treat analysis found RAS‐R scores to be similar between the intervention (mean = 84.7, SD= 15.6) and control (mean = 86.5, SD= 15.3) phases; the adjusted estimated difference in the mean RAS‐R score was −1.70 (95% confidence interval: −3.81 to 0.40; p = .11). Discussion This first trial of an adapted mental health experience codesign intervention for psychosocial recovery outcomes found no difference between the intervention and control arms. Conclusions More attention to the conditions that are required for eight essential mechanisms of change to support codesign processes and implementation is needed. Patient and Public Involvement The State consumer (Victorian Mental Illness Awareness Council) and carer peak bodies (Tandem representing mental health carers) codeveloped the intervention. The adapted intervention was facilitated by coinvestigators with lived‐experiences who were coauthors for the trial and process evaluation protocols, the engagement model and explanatory model of change for the trial.